Comparing the Effect of Evening Primrose oil and Vitex on Hot Flashes in Menopause - bahare Dastenaei motaghi; akram karami; Sedigheh Jamali (Fasa University of Medical Sciences, 2020)
Background & Objective: Due to the numerous complications such as hot flashes in postmenopausal women, this study aimed to compare the effects of two phytogenic herbs including Evening Primrose oil and Vitex on hot flashes in menopause Materials & Methods: The present study was a double blind clinical trial performed on 150 postmenopausal women in 2014 in Chaharmahal and Bakhtiari province. Women who participated in this study randomly used one of the two flowering plants and the vitagnus tablet or placebo twice a day for one month. Copperman's questionnaire was used to measure menopausal hot flash. At the end of a month, the results were analyzed using descriptive and analytical statistics using SPSS software. Results: The results showed that the use of Primrose oil compared to vitagnus had a significant effect on the duration and frequency of hot flashes (P <0.001). However, in reducing the intensity of hot flashes, the two plants had no superiority compared to each other (p = 0.6). Conclusion: Evening Primrose oil is more effective compared to Vitagnes in reducing hot flashes in women.